Neue Klimaschutzregeln für den europäischen Luftverkehr: Chancen und Risiken - Janina Scheelhaase; Wolfgang Grimme; Sven Maertens (Wirtschaftsdienst, 2023)
Die EU-Kommission, das EU-Parlament und der EU-Rat haben sich auf neue Klimaschutzregeln für den europäischen Luftverkehr geeinigt. Ausgehend vom Fit-for-55-Vorschlag der EU-Kommission wird der europäische Luftverkehr in Zukunft stärker zum Klimaschutz beitragen, da die Regelungen des EU-Emissionshandels verschärft und gleichzeitig Anreize zur zunehmenden Nutzung von nachhaltigen Kraftstoffen (Sustainable Aviation Fuels) gesetzt werden. Es wird gezeigt, welche neuen Klimaschutzregeln auf den europäischen Luftverkehr zukommen und welche Chancen und Risiken sich aus ökologischer und ökonomischer Sicht hierdurch ergeben. – – In December 2022, the EU Commission, the EU Parliament and the EU Council agreed on new climate protection policy measures for European air transport within the framework of the so-called trialogue. The trilogue decision means that European aviation will make a greater contribution to climate protection in the future, as the regulations of the EU emissions trading system will be tightened and incentives for the increasing use of sustainable aviation fuels (SAF) will be introduced at the same time. Whether further measures proposed as part of the Fit for 55 package, such as a European kerosene tax, will be introduced in the future is currently open. This paper provides an overview of the new climate protection regulations that will affect European aviation in the future and the opportunities and risks that will arise from an environmental and economic perspective.
Keywords: Q58; L93; 330; Luftverkehr; Klimaschutz; EU-Staaten